BERTEOLOGI DALAM KONTEKS PANDEMI COVID 19: UPAYA MENGEMBANGKAN ETIKA TEOLOGIS DALAM RELASI KEADILAN DAN KEHARMONISAN DENGAN ALAM - Apriani Magdalena Sibarani (Majalah Ilmiah METHODA, 2020)
The Coronavirus (COVID-19) pandemic is a global problem for humans today. There are some hypotheses and analyses regarding the cause of the pandemic, including the ecological problem (environmental damage) which is considered as one of the biggest contributing factors. The natural imbalance and the environmental damage are an undeniable reality in today’s life. The theological understanding of humans as imago Dei who have the rights to conquer and control the nature exacerbate the ecological problems and increase humans’ disharmony with nature. This paper invites the readers to understand the context of this pandemic as an effort to reflect on discriminatory theological views of nature which lead to irresponsible human attitudes and behaviors. In this regard, this paper offers a theological understanding which recognizes relational justice and harmony with nature. This paper also provides an explanation of the relation between COVID-19 and ecological issues, as well as theological views which trigger humans’ destructive attitudes and behaviors towards nature. Moreover, this paper offers solutions to transform the crisis through theological paradigms which become theological ethics, in order to establish the relation between justice and harmony with nature.